Earnings quality, investment decisions, and financial constraint - Carvalho, Flávio Leonel; Kalatzis, Aquiles Elie Guimarães (Review of Business Management, 2018)
Purpose – The purpose of this study was to investigate the relationship between accruals quality, financial constraint, and investment decisions and if earnings quality affects investment-cash flow sensitivities. Design/methodology/approach – An analysis was conducted of a sample with 10,318 observations of 958 non-financial companies from seven different countries, covering 1992 to 2009. Then, the investment determinants were estimated using the Generalized Method of Moments (GMM). Findings – Poor accruals quality was positively associated with investment rates for firms with overinvestment and negatively related to investment rates for firms with underinvestment. Additionally, the results indicate that accruals quality affects investment-cash flow sensitivities for firms in a situation of financial constraint; that is, poor accounting information quality can exacerbate the dependence of investment on free cash flow. Originality/value – The results show that poor accruals quality could exacerbate the problems caused by the conflict of interest between decision-makers and shareholders or other stakeholders.